Evaluation of Arabic Teacher Preparation Program in Faculty of Education at Sana'a University in the Light of Total Quality Standards - Suaad Salem AlSaba; Ahmed Hassan Ghalib; Samah Abdulwahab Ali Abdu (University of Science and Technology, Yemen, 2010)
Evaluation of Arabic Teacher Preparation Program in Faculty of Education at Sana'a University in the Light of Total Quality Standards Abstract   The objective of this research is to evaluate the Arabic teacher preparation program in the Faculty of Education, Sana'a University, in the light of the Total quality standards by answering the following question: v  What is the situation of Arabic Teacher preparation program in the Light of standards of Total quality in the Faculty of Education at Sana'a University? From this main question the fowling questions are branched: v  What are the total quality standards that in their lights the Arabic teacher preparation program can be evaluated in the Faculty of Education at the Sana'a University? v  What is the range of the availability of the admission quality standards? v  What is the range of the availability of total quality standards in the program from viewpoint of the head of Arabic Language department? v  What is the range of the availability of total quality standards in the program from viewpoint of the academic staffs in the department? v  What is the range of the availability of total quality standards in the program from viewpoint of the students? In order to answer these research questions, the following procedures were being followed: • Setting a list of total quality standards for Arabic teacher preparation program in the Faculty of Education, Sana'a University. Standards in the list have been derived from specialized books, studies and past related researches.   • First: Coming up with a list of Total quality standards in that in its lignt. the Arabic teacher program Exposing the list to a group of specialists in the fields of quality, Arabic language curricula and its teaching methods, and measurement and evaluation; to make sure of the list's apparent validity. • The above two steps resulted in the list; consist of 152 standards were supplied on twelve domains of preparing Arabic teacher program. These domains are: the admission policy, the general objectives of the program, objectives of the academic, professional and cultural preparation; practicum and methods of teaching, teaching staffs, equipment and material, academic management, students' assessment, personnel, financial support, and community service. • The standards has been divided into two interview forms, and two questionnaires. The first interview form which consisted of (7) standards, applied with the admission official in the Faculty of Education. The second interview form which consisted of 65 standards applied with head of the program department, while the first questionnaire applied on a sample consisted of (9) members of the academic staff, and the second questionnaire applied on a sample consists of (71) students from the fourth level of Arabic Language curriculum department in the Faculty of Education at Sana'a University.  The findings of the research are as follows: program in The Faculty of Education at Sana'a University has been evaluated  Second: The evaluation on the extent of availability of total quality standards in the program from the research sample viewpoints showed that:  • 57% of the admission quality standards are not satisfied in the program admission policy according to viewpoint of the admission official. • 58% of the quality preparation standards are not satisfied in the program according to viewpoint of the head of Arabic Language department. • 43% of the quality preparation standards are satisfied in the program according to viewpoint of academic staff sample. • 63% of the quality preparation standards are not satisfied in the program according to viewpoint of students' sample.